Odpowiedź:
6.
1/2x - 4 = x - 6
1/2x - x = -6 + 4
-1/2x = -2 /*(-2)
x = 4
7.
5/6(x - 1) = 4
5/6x - 5/6 = 4
5/6x = 4 + 5/6 /*6/5
x = 6/5 * 4 5/6 = 6/5 * 29/6 = 29/5 = 5 4/5
8.
(2x + 3)/5 = (2 - x)/3 - x
2/5x + 3/5 = 2/3 - 1/3x - x
2/5x + 1/3x = -1/3 - 3/5
6/15x + 5/15x = -5/15 - 9/15
11/15x = -14/15 /*15/11
x = -14/15 * 15/11 = -14/11 = -1 3/11
9.
(4x + 7)/2 - (5x - 1)/6 = x + 5
2x + 7/2 - 5/6x + 1/6 = x + 5
1 1/6x - x = 5 - 7/2
1/6x = 5 - 3 1/2 /*6
x = 1 1/2 * 6 = 3/2 * 6 = 9
10.
(x + 5)/4 - (2x + 1)/8 = 1/2(2 - x)
1/4x + 5/4 - 1/4x - 1/8 = 1 - 1/2x
1/2x = 1 - 1 1/4 + 1/8 /*2
x = 2(-1/4 + 1/8) = 2 * (-2/8 + 1/8) = 2 * (-1/8) = -1/4
Szczegółowe wyjaśnienie: